2014
DOI: 10.1111/aogs.12421
|View full text |Cite
|
Sign up to set email alerts
|

Fetal scalp blood sampling in labor – a review

Abstract: During the 1970s and 1980s, electronic fetal monitoring and fetal scalp blood sampling were introduced without robust evidence. With a methodical review of the published literature, and using one randomized controlled trial, seven controlled studies, nine randomized studies of various surveillance methods and data from the Danish National Birth Registry, we have assessed the usefulness of fetal scalp blood sampling as a complementary tool to improve the specificity and sensitivity of electronic cardiotocograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…4 The results of this study demonstrate that the StO 2 and tissue blood pH in mice exhibit a strong positive correlation. Thus, the results of the present study support the conclusion of the previous report that StO 2 during labor is associated with umbilical arterial blood pH.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…4 The results of this study demonstrate that the StO 2 and tissue blood pH in mice exhibit a strong positive correlation. Thus, the results of the present study support the conclusion of the previous report that StO 2 during labor is associated with umbilical arterial blood pH.…”
mentioning
confidence: 53%
“…3 A meta-analysis reported that both FSBS and FHR monitoring during the intrapartum period resulted in avoiding unnecessary operative deliveries. 4 The National Institute for Health and Care Excellence recommends FSBS to assess fetal status when FHR monitoring yields a positive result. 5 Although FSBS is a good test for the management of labor, it is infrequently performed in clinical settings.…”
mentioning
confidence: 99%
“…2 Consequently, such tests are popular and supported by national guidelines in many countries. [3][4][5] Lactate is a direct product of anaerobic glucose metabolism with animal studies demonstrating that levels rise earlier during hypoxia 6 and persist longer 7 than a low pH.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, it helps to identify the suitable technique to deliver. Besides that, it helps to identify the suitable technique to deliver the baby, either by normal birth or caesarean method [4]- [5]. Conventional technique for this test requires the small incision on the fetal scalp and drop of blood is collected using a thin heparinized capillary tube [6].…”
Section: Introductionmentioning
confidence: 99%